Crystalline structure of an ammonia borane–polyethylene oxide cocrystal: a material investigated for its hydrogen storage potential. Issue 31 (6th July 2018) - Ploszajski, Anna R.; Billing, Matthew; Cockcroft, Jeremy K.; Skipper, Neal T.
Abstract : Rare polymer crystal structure formed by ammonia borane in polyethylene oxide exhibiting a snake-like chain through the crystal. Abstract : The crystalline structure of a cocrystal comprising ammonia borane (AB) and a short-chain polyethylene oxide (PEO or PEG) has been determined by single-crystal X-ray diffraction. The components interact via hydrogen bonds between each of the hydrogen atoms at the NH3 end of the AB molecules and alternate oxygen atoms along the PEO backbone. The PEO chains in the structure exhibit an unusual conformation where their curvature reverses every 5 monomers, such that the polymer snakes through the crystal. This is the first time that an AB composite material has been determined to be a cocrystal, and no structure determination of a cocrystal to confine AB has been reported before.